Datasets and methods of product recognition on grocery shelf images using computer vision and machine learning approaches: An exhaustive literature review - Melek, Ceren Guelra; Sonmez, Elena Battini; Varli, Songuel (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
A product recognition system recognizes all products on the shelf images and determines their positions. A business equipped with an automatic product recognition system has a convenient follow-up of many humanpowered activities while increasing customer satisfaction. That is, product recognition stands out with its benefits such as tracking shelf layouts and stocking their status, and improving the shopping experience for customers, especially the visually impaired ones. However, product recognition is a challenging problem of computer vision in terms of the difficulty of obtaining and updating datasets and the breadth of the product scale. On the other hand, the number of studies on product recognition is constantly increasing by using various computer vision and machine learning methods, and effective solutions are offered to this problem. This paper provide a comprehensive review in the field of researches of product recognition on grocery store shelves. In this article, data sets and approaches used in the literature for the development of an automatic product recognition system are examined and compared, and their benefits and limitations are commented. Finally, a guideline is provided for future researchers and new perspectives for future studies are presented.
Keywords: Product recognition; Planogram compliance; Computer vision; Machine learning; Grocery shelf images; Automation & Control Systems; Computer Science; Engineering